1971
DOI: 10.2466/pr0.1971.29.1.160
|View full text |Cite
|
Sign up to set email alerts
|

Heart-Rate Variability in Creative Functioning

Abstract: Average creativity scores for each of 20 Ss in this experiment correlated .49 with a measure of heart-rate variability monitored during an inkblot task. It was suggested that cardiac variability may be greater in the more creative Ss because they shift more from realistic to imaginal modes of thinking than do relatively less creative Ss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…In people with a higher amount of regular exercise, greater HRV increase (i.e., vagal activation) during the creative ideation task was correlated with greater originality of the produced ideas, which is in accordance with some relevant research [40,41]. By contrast, in more sedentary people this association was reversed.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In people with a higher amount of regular exercise, greater HRV increase (i.e., vagal activation) during the creative ideation task was correlated with greater originality of the produced ideas, which is in accordance with some relevant research [40,41]. By contrast, in more sedentary people this association was reversed.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, the observed interaction effect suggests that greater originality in a creativity task is not only achieved by the investment of more mental effort [24,35], and more spontaneous and associative modes of thinking [32], but that both can lead to success, depending, among others, on the physical constitution of the person. This finding may in part explain the heterogeneity of previous results on associations between cardiac vagal control and creative performance [24,35,40].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…There are other physiological correlates of creativity. Thus, it has been indicated that participants scoring high on a variety of creative measures manifested a greater heart-rate variability than did uncreative participants (Bowers & Keeling, 1971), verified recently by Norlander, Bergman and Archer (1997). Following a perusal through the research, Suler (1980) drew the conclusion that greater heart-rate variability in creative participants indicated their rapid cognitive shifts between reality-oriented cognition and more imaginal, inner-directed ideation.…”
Section: Inebriation and Inspiration? A Review Of The Research On Alcmentioning
confidence: 64%